An efficient planar-heterojunction solar cell based on wide-bandgap CH3NH3PbI2.1Br0.9 perovskite film for tandem cell application. Issue 2 (29th October 2015) - Zhu, Weidong; Bao, Chunxiong; Li, Faming; Zhou, Xiaoxin; Yang, Jie; Yu, Tao; Zou, Zhigang
Abstract : The planar-heterojunction solar cell based on wide bandgap CH3 NH3 PbI2.1 Br0.9 perovskite film shows an efficiency of 12.67% with negligible current hysteresis. Abstract : A dense and homogenous flat wide-bandgap (1.75 eV) CH3 NH3 PbI2.1 Br0.9 perovskite film was prepared via a facile halide exchange route. The planar-heterojunction solar cell shows an optimal power conversion efficiency of 12.67% with negligible current hysteresis due to the film's large grains and vertically oriented grain boundaries.